2017
DOI: 10.3389/fevo.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Anaplasma phagocytophilum and Ehrlichia spp. in Opossums and Dogs in Campeche, Mexico: The Role of Tick Infestation

Abstract: In recent years, some tick-borne diseases such as anaplasmosis and ehrlichiosis became widespread worldwide, threatening the health of humans, domestic animals and wildlife. The aims of this study were to determine the presence of Anaplasma phagocytophilum, Ehrlichia canis, and Ehrlichia chaffeensis in 102 opossums (Didelphis spp.) and 44 owned free-ranging dogs in southeastern Mexico using a specific polymerase chain reaction (PCR). A. phagocytophilum was detected in opossums and dogs with a prevalence of 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
(55 reference statements)
0
5
1
2
Order By: Relevance
“…The etiologic agent of human granulocytic anaplasmosis, A. phagocytophilum , was detected in 12.88% of the dogs (25/194). In a study performed in southern Mexico, a prevalence of 27% was found [ 45 ], which is higher than that of the present study. In addition, other studies conducted in the same area as the present study and nearby places showed varying results.…”
Section: Discussioncontrasting
confidence: 90%
“…The etiologic agent of human granulocytic anaplasmosis, A. phagocytophilum , was detected in 12.88% of the dogs (25/194). In a study performed in southern Mexico, a prevalence of 27% was found [ 45 ], which is higher than that of the present study. In addition, other studies conducted in the same area as the present study and nearby places showed varying results.…”
Section: Discussioncontrasting
confidence: 90%
“…En cuanto a las infecciones por A. phagocytophilum, se han diagnosticado cada vez más en animales de compañía y de granja a nivel mundial (McMahan et al, 2016). En México, A. phagocytophilum, se ha detectado en zarigüeyas y perros del estado de Campeche, con una prevalencia de 3 y 27%, respectivamente (Rojero et al, 2017); sin embargo, en este trabajo ninguno de los perros evaluados resultó positivo por PCR o frotis sanguíneo. Esto no es sorprendente, ya que Ixodes spp.…”
Section: Discussionunclassified
“…It is known that the exchange of ectoparasites among these hosts has a central importance in the epidemiology of tick-borne diseases. In this perspective, opossums are suggested to play a central role in the epidemiological chain of some tick-borne pathogens, as one of their behaviors (i.e., movement among forests, urban, and rural locations) facilitates the spreading of different tick species from wild environments to urban sites (Bermúdez et al 2016 ; Rojero-Vázquez et al 2017 ). For example, opossums captured close to human dwellings have been reported harboring species of hard ticks ( Amblyomma spp.)…”
Section: Arthropods and Vector-borne Pathogens Associated With Didelphis Sppmentioning
confidence: 99%